2022
DOI: 10.1097/fjc.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins Promote Endothelial Cell Viability and Angiogenesis

Abstract: Botanic drugs are reportedly effective in treating ischemic conditions by improving vascular circulation. However, it has been very rare for biomaterial researchers to look into the possibility of using such products in the context of tissue regeneration. This work studied 4 botanic drugs to explore their effects on vascular endothelial cell growth. Human umbilical endothelial cells were cultured in the presence of different doses of astragalus powder extract, astragalus injection, puerarin injection, and proa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
2
1
0
Order By: Relevance
“…The PVA, PVA-PG, PVA-VG, and PVA-PG-VG solutions formed manipulable hydrogels after 8 freeze-thaw cycles (Figure 1A). These results follow those reported previously showing the formation of PVA hydrogels after physical (freezethaw) crosslinking (Mandal and Bostanian, 2000;Wang et al, 2022). There was no apparent difference in the shape or morphology of these hydrogels.…”
Section: Shape and Structure Of The Hydrogelssupporting
confidence: 92%
See 1 more Smart Citation
“…The PVA, PVA-PG, PVA-VG, and PVA-PG-VG solutions formed manipulable hydrogels after 8 freeze-thaw cycles (Figure 1A). These results follow those reported previously showing the formation of PVA hydrogels after physical (freezethaw) crosslinking (Mandal and Bostanian, 2000;Wang et al, 2022). There was no apparent difference in the shape or morphology of these hydrogels.…”
Section: Shape and Structure Of The Hydrogelssupporting
confidence: 92%
“…The plates were subjected to 8 cycles of freeze-thaw. Each cycle included incubation at −80 °C for 1 h to freeze the solution; then, the plates were moved to room temperature to thaw the solution (Wang et al, 2022). The designed hydrogels were then used for subsequent experiments.…”
Section: Preparation Of Hydrogelsmentioning
confidence: 99%
“…To investigate the role of DDNs in MI/R injury, we used HUVECs to study the effects of DDNs on promoting angiogenesis in vitro. The choice of HUVECs for cellular uptake, proliferation, and migration studies is based on their relevance to angiogenesis and physiological similarity to endothelial cells in vivo [41]. We confirmed that DDNs can promote the proliferation and migration of HUVECs in vitro and increase microvessel density in MI/R mice.…”
Section: Discussionsupporting
confidence: 63%